Politeness strategies implemented by native speaker teachers versus non-native speaker teachers in a classroom of english as a foreign language in vietnam - Bảo Nam Lộc (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis focuses on politeness strategies proposed by Geoffrey Leech, Brown and Levinson’s face, Robin Lakoff, Watts with discourse politeness, Roots of Linguistic Politeness of Austin, Grice and Searle with references to both English and Vietnamese and its realization in a classroom discourse. The theoretical part describes the most influential politeness theories and also findings on the topic of teaching pragmatics and linguistic politeness. The research focuses on analysis of teachers’ verbal realizations of politeness as found in the recordings of four English lessons. The research was designed to verify the two hypotheses: the first one is that teachers are basically polite in a classroom of English as a foreign language and the last one is that politeness strategies of Vietnamese teachers of English differ from those of native speaking teachers. The analytical part adopts the viewpoint of Brown and Levinson’s positive and negative politeness. Then some conclusions were withdrawn hopefully to help learners with some politeness strategies that may be useful for them when they have to face with doing Face Threatening Acts. Finally, some implications were put forward for the teaching and learning of English as a foreign language in Vietnam